Effects of xylooligosaccharide supplementation on performance, intestinal morphology, antioxidant capacity and cecal microflora in weaning pigs - Ma, Wenfeng; Gao, Mengmeng; Zhang, Xiaoli; Wu, Xiaohong; Mao, Pei; Fan, Wenna; Zhao, Lingping; Tan, Shitu (Frontiers in Veterinary Science, 2025)
Study aimed to investigate the effects of xylooligosaccharide (XOS) supplementation on growth performance, antioxidant capacity, and cecal microorganisms in weaned pigs. Forty-eight 28-day-old hybrid weaned pigs Duroc × (Landrace × Yorkshire) of similar body weight (7.62 ± 0.41 kg) and genetic background were randomly divided into control group (CON) and experimental group (XOS). The CON group was fed a basal diet, and the XOS group was fed a diet supplemented with 500 mg/kg XOS. The pretest period lasted for 7 days, and the test period lasted for 28 days. Compared with the CON group, the XOS group significantly reduced the feed-to-gain ratio by 5.14%, increased alkaline phosphatase activity in serum, and improved the apparent digestibility of dietary ether extract (EE) and calcium (Ca) in weaned pigs (p < 0.05). In addition, XOS supplementation increased the villus height of the duodenum by 9.69% and that of the ileum by 11.64%, and decreased the crypt depth of the jejunum by 21.37% (p < 0.05). XOS supplementation increased superoxide dismutase (SOD) activity in serum and ileum by 10.48 and 48.43%, respectively; increased catalase (CAT) activity in serum, liver, and spleen by 34.96, 29.55 and 90.36%, respectively; and decreased the malonaldehyde (MDA) content in liver and spleen of weaned pigs by 35.66 and 33.85%, respectively (p < 0.05). Compared with the CON group, the cecal microbial community diversity of weaned pigs with XOS supplementation significantly differed (p < 0.05). XOS supplementation reduced the relative abundance of Proteobacteria and Spirochaetes in the cecum of weaned pigs, and improved the relative abundance of Lactobacillus and Ruminococcus in the cecum of weaned pigs, but decreased the relative abundance of Spirillaceae NK4A136, Prevoid group, and AC2044 group of Spirillaceae (p < 0.05). In conclusion, the dietary inclusion of 500 mg/kg of XOS increased the growth performance, apparent digestibility, and intestinal morphology of weaned piglets, stimulated the proliferation of probiotic microorganisms, and improved the antioxidant capacity of pigs. The results of this study can provide a certain theoretical basis for the application of XOS in weaned piglets.